Calidad de vida, resiliencia y depresión en adultos mayores de Montería, Colombia (2021)
The objective of this study was to determine the relationships between quality of life, resilience and depression in older adults living in the city of Montería. The sample was composed by a group of 100 older adults of both genders, with reading and writing abilities, without presence of cognitive deterioration. As measurement instruments, CASP -19 was used to evaluate quality of life, and CD-RISC 10 to evaluate resilience and to evaluate depressive symptoms CES - D. We worked with a non-experimental design of transversal cut and a descriptive correlational scope. The results showed high scores in the quality of life dimensions of CASP 19, control, pleasure, and self-realization. On the other hand, high scores in resilience and low scores in depression were also observed. There were positive correlations between resilience and the sub-dimensions of the CAPS -19 quality of life scale and negative correlations between depression and the sub-dimensions of the CAPS-19 quality of life scale. Results discussed based on the findings.